Tax Law Enforcement and Its Impact on Restorative Justice and Islamic Law in Tax Crime Cases - Mubarok, Muhammad Husni; Mubarok, Muhamad Zaki; Riza, Muhammad Himmatur; Basir, Sayidah Asma (Fawaid : Sharia Economic Law Review, 2026)
This study aims to analyze the dynamics of tax law enforcement in Indonesia, which faces significant challenges in balancing legal certainty with the recovery of state financial losses. Specifically, this research explores the implementation of Article 44B of the Law on General Provisions and Tax Procedures as a crucial instrument reflecting a restorative justice approach in handling tax crime cases. Through content analysis of policies, law enforcement practices, and expert reviews, this study examines the mechanism of terminating investigations through the settlement of state losses The research findings indicate that a restorative justice approach in the fiscal realm is more effective in recovering state finances compared to a retributive approach solely oriented toward punishing the perpetrator. From an Islamic law perspective, this approach aligns with the principles of public interest (maslahah) and the restoration of circumstances; taxes function as a primary instrument to achieve social welfare in a just and sustainable manner. Nevertheless, this research notes limitations such as challenges in inter-agency coordination and differing perceptions among law enforcement officials, which could potentially reduce the deterrent effect. Overall, this mechanism offers an opportunity for the creation of a tax legal system that is more just, proportional, and oriented toward public benefit. Keywords: Islamic Law; Restorative Justice; Tax Crimes; Tax Law Enforcement.